Pengembangan Kapasitas Kewirausahaan dan Desiminasi Teknologi Pada Kelompok Usaha Kecil di Kertasari Kabupaten Bandung - Dindin Abdurohim; Asep Dedy Sutrisno; Jaka Rukmana (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2020)
Kertasari Regency of Bandung, not only as a center for potatoes in West Java, also proves itself as one of the regional suppliers of national potato needs. The quality of potatoes is not inferior, the target markets are a number of regions, such as Jakarta, Sumatra, Kalimantan, and several other regions. able to penetrate the export market, especially Singapore and a number of well-known supermarkets in Indonesia. Based on the results of interviews and observations on small business groups in the village of Cibereum, said the products processed potato chips produced are still traditional, which are sold to the surrounding area, but the quality of the production of potato chips is not in accordance with market demands. The main problems faced by partner business groups related to the Capacity of Entrepreneurship and Technology used are still limited. the implementation of this activity, began to be carried out in April 2019 - September 2019. The approach method used includes; Technology Design, Technology Making, Technology Operation Test, Dissemination / Training, Technical Guidance, Assistance, Business Facilitation and Mediation. The results of the implementation of Entrepreneurship Capacity Development and Technology Dissemination have a positive impact on the Partner business group, this can be seen from the implementation of science and technology through the Training Approach, Technical Guidance and Technology Assistance and Application can solve the problem by providing the following solutions: 1) Achievement of Entrepreneurial Capacity Partners: a) Partners Have High Motivation in carrying out their business, b) Partners Able to Run Business Management right, c) Partners Have a Business Plan as a business guide, d) Partners Are Able to determine Market Opportunities and Market / Business Networks. And 2) Achievements of Technology Application for Partners: a) Partner business group obtains Potato Peeling and Washing Machine (Peeler Machine), Wave Potato Slicer, Spiner, Product Packing Machine and Bag Sealer. b) The Production Process Is More Effective and Can Produce Lots. c) Ability / Skill of Partners increased 100%, d) Increased Products produced both in quality and quantity.